Molecular detection and analysis of beak and feather disease viruses in Iran - Dolatyabi, Sara; Peighambari, Seyed Mostafa; Razmyar, Jamshid (Frontiers in Veterinary Science, 2022)
The beak and feather disease virus (BFDV) is one of the few pathogens capable of causing extinction of psittacines. To determine the prevalence and the nature of BFDV mutation, this study investigated the presence of the BFDV among 1,095 individual birds of the 17 psittacine species in Iran followed by analyzing the DNA sequences of seven replication-associated protein (rep) and 10 capsid (cap) genomes of the virus. The BFDV was found to be the foremost pathogen among more than 12 psittacine species, and phylogenetic analysis showed that the BFDV GenBank-published sequences from Poland, Saudi Arabia, South Africa, Taiwan, and Thailand were most similar to those of this study. Evolutionary analysis concluded that arginine, leucine, and glycine were the amino acids frequently involved in the least-conserved substitution patterns of BFDV, and conversely, methionine, glutamine, and tryptophan were the amino acids that exhibited ultra-high conservation through the substitution patterns. The high substitution rate of arginine to lysine and glycine to serine also made greater contribution to the BFDV gene mutation. The relative synonymous codon usage between two genes revealed that the cap genome encoded proteins frequently used fewer codons, while the rep genome encoded proteins used more codons only at moderate frequency, explaining the broader divergence of the cap compared to the rep sequence. The data analysis also introduced a new variant of BFDV that exists in the rep and cap sequences of budgerigars. While the existence of more new variants was suspected, more solid evidence is required to substantiate this suspicion.